1973
DOI: 10.1017/s0021859600086470
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary deficiencies of energy, protein and calcium on the pregnant ewe: V. Chemical analyses and histological examination of some individual bones

Abstract: The effects of low protein and low Ca intakes during pregnancy on the chemical composition and histological appearance of selected bones of ewes and lambs is reported. Twenty-eight 6£-year-old Blackface ewes were used in a 2 x 2 experiment in which semi-purified diets containing 11-8 and 6-0% crude protein and 1-2 and 0-11% Ca in the dry matter were offered in amounts designed to induce a level of undernutrition typical of that experienced by hill sheep in winter. I n addition, six sheep were killed in early p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

1975
1975
2008
2008

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(6 citation statements)
references
References 16 publications
1
5
0
Order By: Relevance
“…Antler growth had ceased 6 months earlier and the bones could therefore be expected to be well mineralized. By comparison with these and data for well nourished sheep (Sykes, Nisbet & Field, 1973), the bones of the present stags were poorly mineralized ( Table 3). The higher specific activity of "Ca in bone ash in the rib and vertebra (Table 3) further indicates the relative sensitivity of these bones to remodelling during mineral deficiency as has previously been observed by Benzie et al (1956) in sheep.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…Antler growth had ceased 6 months earlier and the bones could therefore be expected to be well mineralized. By comparison with these and data for well nourished sheep (Sykes, Nisbet & Field, 1973), the bones of the present stags were poorly mineralized ( Table 3). The higher specific activity of "Ca in bone ash in the rib and vertebra (Table 3) further indicates the relative sensitivity of these bones to remodelling during mineral deficiency as has previously been observed by Benzie et al (1956) in sheep.…”
Section: Discussionmentioning
confidence: 52%
“…Degree of mineralization (ratio of ash: organic matter) and specific radioactivity (SA) in stags 589 and 103 was determined during the period of maximum rate of Ca deposition and 13 days after injection of 800 fid "Ca as CaCl 2 . Values for replete animals are from a stag which died in mid-winter and for well fed ewes during late pregnancy, from Sykes, Nisbet & Field (1973). Rate of deposition of Ca during the balance period was calculated from the data of Muir et al (1987).…”
Section: Methodsmentioning
confidence: 99%
“…It is likely, however, that factors which, independently of the Ca homeostatic mechanism, affect net transfer of Ca between the skeleton and the plasma and extracellular pool of Ca will complicate the relation. An example is the loss of bone matrix as a result of protein deficiency (Frandsen et al 1954;El-Maraghi et al 1965;Sykes et al 1973). Indeed, in grazing studies with sheep during the same stage of lactation as in the present study, Sykes & Geenty (1986) observed that, on average, a 1.8 g/kg body-weight per d reduction in N balance was associated with a 10 mg/kg body-weight per d reduction in the calculated rate of Ca absorption though, as would be expected, the absolute rate of absorption of Ca at any daily N balance was dependent on milk Ca output.…”
Section: Discussionmentioning
confidence: 99%
“…The 20% loss of tissue N is a different matter. It not only implies a degree of protein deficiency directly detrimental to the normal protein metabolism of the body but it may also induce an inevitable loss of calcium from the skeleton as a consequence of the bone matrix erosion that accompanies protein deficiency (Sykes et al 1973;Sykes & Geenty, 1985).…”
Section: Body Composition Of Farm and Laboratory Animals 75mentioning
confidence: 99%